2021
DOI: 10.1002/bio.4122
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence and crystal structure of SrLa1−xAlO4:xEu3+ phosphor synthesized using a sol–gel method

Abstract: The SrLa 1Àx AlO 4 :xEu 3+ phosphors were obtained using one calcination of a precursor synthesized using a sol-gel method. When excited at 396 nm, this phosphor emits a red light mixed with several strong peaks centred at 596 nm, 616 nm and 625 nm, attributed to 5 D 0 ! 7 F 1, 2 transitions of Eu 3+ ions, respectively. The concentration quenching occurs at x = 1.5 mol% mol of SrLa 1Àx Eu x AlO 4 and the critical energy transfer distance is calculated to be 13.13 Å, the dipole-dipole interaction was found to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…The color purity showed that an intense red color was emitted for Eu-doped SrLaAlO 4 phosphors with 53.1 % for 0.10 mol.% concentrations of Eu 3+ . In comparing with the investigation by Yan et al [14], we observed increasing the Eu 3+ dopant concentration to 0.10 mol.% reduces the chromaticity coordinates, color purity and CCT as observed in Table 2. The proposed energy diagram of SLA Eu in Fig.…”
Section: Down-conversion Luminescence Properties Of Sla:eusupporting
confidence: 75%
See 1 more Smart Citation
“…The color purity showed that an intense red color was emitted for Eu-doped SrLaAlO 4 phosphors with 53.1 % for 0.10 mol.% concentrations of Eu 3+ . In comparing with the investigation by Yan et al [14], we observed increasing the Eu 3+ dopant concentration to 0.10 mol.% reduces the chromaticity coordinates, color purity and CCT as observed in Table 2. The proposed energy diagram of SLA Eu in Fig.…”
Section: Down-conversion Luminescence Properties Of Sla:eusupporting
confidence: 75%
“…SrLaAlO 4 belong to the ABCO 4 -kind layered perovskite compound as a host lattice where A represents the alkaline earth divalent metallic ion, B represents the trivalent lanthanide ion while C represents any trivalent transition metal ion [13]. This research is novel and has not been investigated in contrast to the reports by Yan et al on Eu doped SrLaAlO 4 who used sol-gel as their synthesis method and lower Eu-dopant concentration (0.0 -0.025 mol.%) [14]. The aim of this research is to investigate the structural, morphological, optical and photoluminescence properties of 0.10 mol.% Eu doped SrLaAlO 4 phosphors by combustion synthesis method.…”
Section: Introductionmentioning
confidence: 94%